Analysis of the situation in agriculture of the stavropol territory under the influence of the COVID-19 pandemic - A. V Chernyavskaya (Вестник Северо-Кавказского федерального университета, 2022)
Agriculture in the Stavropol Territory is one of the main branches of the economy, actively replenishing budgets of all levels. Local farmers ensure food security not only in the region, but also in the country, producing high-quality products. The agro-industrial complex of the Stavropol Territory has noticeably felt the impact of the COVID-19 pandemic. By the end of 2020, there was a sharp reduction in the volume of crop production, with a slight increase in the cost of livestock products. The analytical data of the article reveal all the features of farming in the pre-pandemic and post-pandemic period. The analysis of the situation in the agro-industrial complex of the region should include four stages, each of them plays its own specific important role in the entire study.